Accumulative and adaptive responses of maize transpiration, biomass, and yield under continuous drought stress - Cui, Yi; Tang, Huiyan; Zhou, Yuliang; Jin, Juliang; Jiang, Shangming (Frontiers in Sustainable Food Systems, 2024)
Introduction Continuous drought stress aggravates agricultural losses and threats food security. However, the responses of crops to continuous drought stress remain uncertain. Methods To make up the limitations of field experiment and achieve the setting of multiple continuous drought stress scenarios, AquaCrop model is calibrated and validated using field experiment data of summer maize in 2017 and 2018 seasons. Then, the whole growth processes under different continuous drought stress scenarios at two growth stages of maize are simulated. The quantitative responses of transpiration (Tr), biomass accumulation, and yield formation to continuous drought stress are analyzed. Results and discussion The results show that when the maize encounters serious drought at the seedling stage, the reduction rates of Tr at the jointing stage, the tasseling stage, and the milking stage are 57.45%, 43.61%, and 5.24%, respectively. Drought stress at a growth stage of maize not only have negative impacts on transpiration and biomass accumulation at this stage, but also have after-effects on these elements at the subsequent stages. In addition, continuous serious drought at the seedling and jointing stages reduces yield by 100%, which is higher than the sum of the loss rates at these two stages [>33.30% + 24.16%)], while the loss rate due to continuous light drought is lower than the sum [20.66% < (18.80% + 12.45%)]. The impact of continuous drought stress at two growth stages generally exceeds the sum of the impacts of the two single stages. Nevertheless, drought at the seedling stage promotes the adaptability of maize to drought, alleviating the negative impacts of light drought at the jointing stage, while the adaptability disappears when drought at the jointing stage is serious. Therefore, in the actual production of maize, serious drought at the seedling stage should be avoided to ensure seed survival. Meanwhile, continuous drought at the seedling and jointing stages should be prevented to reduce the severe accumulative effects, which guides drought disaster reduction and sustainable agricultural production.